Revitalizing the library for the nation : proceedings of the 7th International Conference on Libraries, Information and Society held on 18-19 April 2019 at Hatten Hotel, Melaka - Mohd. Khalid, Yanti Idaya Aspura (Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya and University of Malaya Library, 2019)
Organised by: Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya and University of Malaya Library.